Depression and repression: Global capitalism, economic crisis and penal politics in interwar Greece - Cheliotis, Leonidas (European journal of criminology, 2022)
Notwithstanding the significant advances made over the last twenty years in terms of charting and explaining the ways in which state punishment is influenced by economic and political forces, little is still known about the penal effects of conditions of economic crisis and about the role the incumbent government's political orientation plays in this regard. Because the few available studies on these questions have been preoccupied with the Anglo-American sphere and only in the context of recent decades at that, even less is known either about the implications that different types or experiences of economic crisis carry for state punishment, or about the influence exerted in this respect by government political orientations other than those found in established democracies. Irrespective of geographical or temporal scope, moreover, the impact that different extranational factors and actors may have in terms of economic, political or directly penal matters domestically remains poorly understood. With a view to helping fill these gaps in the literature, this article explores the effects on state punishment that economic crisis and government political orientation had in interaction with one another in the context of interwar Greece. Attention is first paid to various ways in which global capitalism was decisive in creating within Greece an environment conducive to increased punitiveness on the part of the state. The focus is on the economic, social and political consequences of the Wall Street crash of 1929 and Britain's exit from the gold standard in 1931, as these were exacerbated by Greece's long-term exposure to predatory lending, speculative investing and external interference in her domestic affairs in the context of engaging international capital markets. The article then proceeds to discuss how the Liberal government of 1928-1932 sought to handle the situation, particularly the approach it took towards punishment.